Transducers-to-microcntroller interfaces-software solution approach - Adetunji, Lawal Wahab; Abdulaziz, Salami Femi; Khan, Sheroz; Alam, A. H. M. Zahirul; Islam, Md. Rafiqul; Hameed, Shihab A.; Hassan Abdalla Hashim, Aisha (IIUM Press, 2011)

(untitled)
Health interfacing circuits serves as platforms through which data signals are passed from one acquisition or processing stage to another. The purpose of these platforms vary and could be for the purpose of eliminating some signal components that are not required in the content of data that is moved onward or for the purpose of squeezing an out of range signal into what is said to be within the safe range of the upcoming stage of processing. Interfacing devices could also be a chain of electronic components providing a preliminary stage of processing or decision required for making a processor or plant to start and stop some onward control activities